2014
DOI: 10.1177/0004563214542289
|View full text |Cite
|
Sign up to set email alerts
|

A novel deletion in the iron-response element of the L-ferritin gene, causing hyperferritinaemia cataract syndrome

Abstract: A 47-year-old woman, presenting to her family physician with fatigue, was incidentally found to have persistently elevated ferritin. There was clinically no suggestion of iron overload, and laboratory testing showed transferrin saturation at the low end of the reference range. After ruling out acquired causes of hyperferritinaemia, as well as laboratory interference, further questioning revealed a history of bilateral early-onset cataracts, allowing a diagnosis of hyperferritinaemia cataract syndrome to be mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Frequent mutations are c.-168G>C/T/A, c.-161C>G/T/A, and c.-160A>G [9]. Small deletions have also been defined [11]. In our study, we found c.-160A>G mutation in 17 patients from 6 families assessed from the provinces of Kayseri and Nevşehir in Turkey.…”
Section: Discussionsupporting
confidence: 49%
“…Frequent mutations are c.-168G>C/T/A, c.-161C>G/T/A, and c.-160A>G [9]. Small deletions have also been defined [11]. In our study, we found c.-160A>G mutation in 17 patients from 6 families assessed from the provinces of Kayseri and Nevşehir in Turkey.…”
Section: Discussionsupporting
confidence: 49%
“…To determine if this small region was important for conferring iron-responsivity, we deleted an 18 nucleotide sequence from the predicted IRE (bases 2-25 of the predicted sequence), to create a tdTomato fitΔIRE line (Figure 5A). Deletion of the IRE has previously been shown to abolish IRE function in other transcripts (Garber and Pudek, 2014;Volz, 2021). Using this line, we assayed transcript abundance in the tdTomato fitΔIRE reporter line at 18 hours of treatment, the peak of response from the above time course (Figure 4A).…”
Section: Removal Of the Ire-like Element From The Fit 3' Utr Reduces ...mentioning
confidence: 99%